Seven Modules on Nutrition Developed by AVRDC, AMEDD and ICRISAT - L'Association Malienne d'Eveil au Developpement Durable; World Vegetable Center; International Crops Research Institute for the Semi-Arid Tropics (International Food Policy Research Institute, 2015)
The topics treated during the nutrition field school sessions were (1) nutrition of children between six and 24 months and preparation of enriched porridge using whole grain millet, (2) nutrition of pregnant and breast feeding (nursing) mothers and preparation of enriched peanut sauce and (3) auto-diagnostic of nutritional status of children between 6 months and 5 years and prevention of Vitamin A, iron and iodine deficiency (4) Food needs of sick children and the preparation of sorghum porridge enriched with legumes; (5) Food Groups: Proteins and preparation of enriched leaf sauce; (6) Food groups that provide energy: Carbohydrates and lipids, and cooking of Laro; (7) Food Groups: Vitamins and minerals and preparation of ?to? from soyabean flour. During each session the essential hygiene and nutrition messages, as identified by the Helen Keller International were also repeated. Project title: Sustainable Intensification of Key Farming Systems in the Sudano-Sahelian Zone of West Africa